2023
DOI: 10.35542/osf.io/djs4b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the validity of a single-item instrument for assessing pre-service primary school teachers’ sense of belonging to science

Abstract: Current research indicates that pre-service primary school teachers’ sense of belonging to science is decisively related to their professionalization in teaching science. Nevertheless, because only very few studies have examined pre-service teachers’ sense of belonging to science so far, further research in this regard seems both reasonable and necessary. To this end, there is a need for instruments enabling a valid assessment of pre-service primary school teachers’ sense of belonging to science. However, exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the other hand, studies (conducted in Germany) that address pre-service primary teachers' interest, academic self-concept, and sense of belonging regarding natural and/or social sciences are scarce (e.g., Beudels et al, 2021;Feser & Plotz, 2023;Lenzgeiger, 2022;Reichhardt, 2018;Wang & Sneed, 2019). Studies focusing on natural sciences have found that these affective-motivational orientations, although distinguishable, tend to be substantially correlated with one another (Feser & Plotz, 2023;Wang & Sneed, 2019). An analogous finding looms for social sciences.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies (conducted in Germany) that address pre-service primary teachers' interest, academic self-concept, and sense of belonging regarding natural and/or social sciences are scarce (e.g., Beudels et al, 2021;Feser & Plotz, 2023;Lenzgeiger, 2022;Reichhardt, 2018;Wang & Sneed, 2019). Studies focusing on natural sciences have found that these affective-motivational orientations, although distinguishable, tend to be substantially correlated with one another (Feser & Plotz, 2023;Wang & Sneed, 2019). An analogous finding looms for social sciences.…”
Section: Introductionmentioning
confidence: 99%